BERNARDO O'HIGGINS NATIONAL PARK/KAWESQAR WAES LAND: CONSERVATION AND MANAGEMENT IN AN ANCESTRAL LAND - Aravena Donaire, Juan Carlos; Vela-Ruiz, Germaynee; Torres, Juliana; Huenucoy, Carolina; Tonko, Juan-Carlos (My University, 2018)
The management of protected areas and the conservation of its natural resources is a matter continuously discussed and subjected to different approaches. Today excluding people from national parks is politically infeasible and ethically unjustifiable, moreover, recognition of humans rights living in or adjacent to protected areas have also been increasing. Therefore, approaches have changed from a preservationist to cooperative and participatory; especially in developing countries, where the human being and their activities should be consistent with conservation objectives, without ignoring the needs of those who live within or adjacent to these territories. In this paper we present our experience developing the management plan of the Bernardo O'Higgins National Park (BONP), the largest in our country. Within the research work, the basal line of natural resources of this national park, the different uses zones and the economic potential associated with touristic activities were defined. The local communities' goals, of those who have been historically involved with the protected area were incorporated, resulting in a management plan that includes in a more participatory way the local community. During the development of this project we achieve non-expected results that exceeded our original objectives: i) we confronted the established use of the regional's coastline areas forbidding aquiculture activities within the BONP limits. ii) Defined fiords and channels as part of the protected area which would enlarge the National Park and transform it into a marine protected area. iii) The participation of the Puerto Eden's Kawesqar community in all the BONP planning process, from the field data collection, through the use zones definition, and the discussion of the management plan of the protected area.
Keywords: kawesqar territory; conservation; management; protected areas